Modeling and Control of Omnidirectional Robots with Displaced Center of Mass - Gallo, Luis (2022)
This work focuses on the design and implementation of a control algorithm for tracking trajectories of an omnidirectional robotic platform. The design is based on a dynamic model that considers the center of mass displaced; this model is obtained by formulating Euler–Lagrange considering the kinetic energy that acts on the robotic system. This type of model is used for when robots carry loads and these are not located in the center of the robot directly affecting the dynamics of the robotic platform; validation of the obtained model is carried out experimentally with an identification algorithm using the robotic platform built.